Waste Management Towards Community Welfare and a Sustainable Environment - Kusumaningrum, Bintari Ratih; Kartika, Annisa Wuri (Journal of Innovation and Applied Technology, 2023)
Effective and sustainable waste management is a crucial issue to maintain the welfare of society and the environment. A comprehensive approach to waste management involves three main pillars such as waste sorting, recycling and technology-based waste management. Waste management aims to maximize the value of waste by converting it into recyclable materials. The waste that is the focus of this activity is household waste and agricultural straw waste. The forms of community service carried out include socializing waste processing, forming work teams and assisting with the waste management process. The results of this activity are increased public knowledge regarding waste management, the formation of a team responsible for waste management, and waste processing products that can be utilized, namely compost and biodegradable pots. The benefit of the activity is reducing the impact of environmental waste into recycled goods to create a cleaner and healthier environment. The next suggestion is to increase cooperation between the village government and the Environmental Service to maximize the program.